Особливості розвитку креативності як умови професіоналізму та особистісного зростання фахівця - Вергелес, К. В. (НТУ "ХПІ", 2011)
У статті вивчалося значення креативності у самореалізації особистості та її самовдосконаленні в якості фахівця. Були розглянуті різноманітні види креативності, серед інженерів досліджені особливості її розвитку. Проаналізована роль даного явища в професійній культурі фахівця. Доведена необхідність розвитку творчого мислення у інженерів для стимулювання особистісного зростання та професіоналізму

In the article the role of creativity in self-realization and selfimprovement of personality as a specialist was studied. Different types of creativity among engineers were examined; the features of its development were investigated. There was analyzed the role of the given phenomenon in the professional culture of the specialist. There was proved the necessity of development of creative thinking at engineers in order to stimulate the personal growth and professionalism
Peculiarities of the development of creativity as conditions of professionalism and personal growth of the specialist
Keywords: самореалізація; саморозвиток особистості; професійна культура фахівця; інженери; творче мислення